Comparison of Efficacy of Dapsone 5% Gel Vs Clindamycin 1% Gel in Mild to Moderate Acne Vulgaris - Iqra, Soonha; Rabia Ghafoor, Rabia Ghafoor; Ali, Asif; Qadir, Misbah Zari; Muhammad Khurram (Indus Journal of Bioscience Research, 2025)
Background and Aim: Acne vulgaris is the most prevalent dermatology condition causing pleomorphic disorder that usually affects individual aged 12 to 25 years with varying prevalence from 50% to 95% in various countries. It can have a significant psychological impact on young people as it primarily affects their face. The present study aimed measure the efficacy of clindamycin 1% versus dapsone 5% gel in patients with mild to moderate acne vulgaris. Materials and Methods: This randomized controlled trial investigated 64 acne vulgaris cases (mild-moderate) in the outpatient department of Dermatology, Jinnah Postgraduate Medical Center (JPMC), Karachi from April 2024 to September 2024. Acne vulgaris patients of either gender having age 20 to 65 years enrolled. Patients were categorized into two groups: Group-I (CLINDAMYCIN 1% GEL) (N=32) and Group-II (DAPSONE 5% GEL) (N=32). Each group received clindamycin 1% gel or dapsone 5% gel once daily night for 12 weeks (about 3 months). Global Acne Grading Scale used for improved efficacy in both groups. Patients achieving post-treatment score ≤ 18 referred as efficacy. Data analysis done using SPSS version 27. Results: The overall mean age of Group-I and Group-II patients was 25.64±6.50 years and 23.96±4.82 years, respectively. Of the total 64 patients, there were 29 (45.3%) male and 35 (54.7%) female. Female patients dominated both groups. Clindamycin group showed promising outcomes in terms of efficacy than Dapsone group. A significant variance in efficacy observed in stratification by age and gender, particularly among patients with duration of acne onset ≤ 3 months. Conclusion: Clindamycin 1% gel showed promising results in terms of effectiveness and efficacy in treating acne vulgaris as compared to Dapsone 5% gel, allowing for once-daily topical application for 12 weeks (3 months).